Challenges and opportunities for meningococcal vaccination in the developing world. Issue 5 (4th May 2018) - Shaker, Rouba; Fayad, Danielle; Dbaibo, Ghassan
ABSTRACT: Meningococcal disease continues to be a life threatening infection with high morbidity and mortality even in appropriately treated patients. Meningococcal vaccination plays a major role in the control of the disease; however, implementing vaccination remains problematic in the developing world. The objective of this review is to identify the challenges facing the use of meningococcal vaccines in the developing world in order to discuss the opportunities and available solutions to improve immunization in these countries. Inadequate epidemiologic information necessary to implement vaccination and financial challenges predominate. Multiple measures are needed to achieve the successful implementation of meningococcal conjugate vaccination programs that protect against circulating serogroups in developing countries including enhanced surveillance systems, financial support and aid through grants, product development partnerships that are the end result of effective collaboration and communication between different interdependent stakeholders to develop affordable vaccines, and demonstration of the cost-effectiveness of new meningococcal vaccines.